As the SARS-CoV-2 virus evolves, should Omicron subvariant BA.2 be subjected to quarantine, or should we learn to live with it? - Xu, Ren; Wang, Wanning; Zhang, Wenlong (Frontiers in Public Health, 2022)
It has been nearly 35 months since the COVID-19 outbreak. The pathogen SARS-CoV-2 has evolved into several variants. Among them, Omicron is the fifth variant of concern which have rapidly spread globally during the past 8 months. Omicron variant shows different characteristics from previous variants, which is highly infectious, highly transmissible, minimally pathogenic, vaccine and antibody tolerant; however, it is less likely to cause severe illness, resulting in fewer deaths. Omicron has evolved into five main lineages, including BA.1, BA.2, BA.3, BA.4, and BA.5. Before BA.5, Omicron BA.2 sublineage was the dominant strain all over the world for several months. The experience of prevention and treatment against BA.2 is worth studying and learning for overcoming other Omicron subvariants. Although the Omicron subvariant BA.2 is significantly less severe than that caused by ancestral strains, it is still far more dangerous than influenza, and its long-term sequelae are unknown. Effective treatments are currently limited; therefore, effective defense may be the key to controlling the epidemic today, rather than just “living with” the virus.